Quality of life after breast reconstruction by DIEP – literature analysis - Anna Dyszy, Sabina (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2021)
Women who are treated for breast cancer experience traumatic experiences that greatly reduce their quality of life. The development of medicine made it possible to find new solutions in surgical treatment. There have been significant advances in the treatment of breast cancer. Surgical treatment very often requires reconstruction of a breast that has been amputated. There is increased interest in the quality of life after medical procedures, especially in plastic surgery, where the assessment of the number of complications is insufficient. In order to be able to help patients effectively, the patient needs to carefully evaluate the treatment. The aim of this study was to evaluate the quality of life of women who were operated on for breast cancer using the DIEP method. This allows for a better understanding of the needs and selection of a method for sick women during preoperative consultation. The analysis was based on a literature review.